PERSEPSI SISWA KELAS VIII TERHADAP PERAN GURU BK DALAM MEMBERIKAN LAYANAN INFORMASI DI SMPN 1 SEMPU - Icha Febrianing Sari; Miftahul Arifin; Ratna Wulandari (Program Studi Bimbingan dan Konseling, 2022)
This study aims to determine the relationship between students' perceptions of the role of BK teachers in providing information services at SMPN 1 SEMPU. This type of research is descriptive quantitative. The research population is class VIII students and uses proportional random sampling technique. The results showed that the results showed that the effective contribution of the variable perception of class VIII students to the role of BK teachers in providing information services at SMPN 1 SEMPU was 57.5%. So that there are 42.5% related to student perceptions not examined in this study. It can be concluded that there is a significant positive relationship between the perceptions of class VIII students on the role of BK teachers in providing information services at SMPN 1 SEMPU. This means that the higher the role of the BK teacher in providing information services, the higher the student's perception will be. On the other hand, if the role of the counseling teacher in providing information services is low, the student's perception will also be low